SPEECH COMMUNICATION: STRUCTURE, TYPES, FORMS AND COMPLICATES - Belyaeva, E.N. (World of Medicine and Biology, 2015)
The structure, types and forms of speech communication were analyzed in the article. The categories “communication” and “speech interaction”, “text” and “discourse” were differentiated. The nature of notions “communicative situation”, “communicative act”, “communicative intention” were defined. The factors providing effective communication and factors that complicate it were precised.
Keywords: communicative situation; communicative intention; understanding; “noises”; text; discourse; typical mistakes